Living in Silverado : Secret Jews in the Silver Mining Towns of Colonial Mexico - Gitlitz, David M. (David Martin) (Book collections on Project MUSE., 2019)
"In this painstakingly researched study David Gitlitz traces the lives and fortunes of three clusters of sixteenth-century crypto-Jews in Mexico's silver mining towns. His narrative paints a vivid portrait of their struggles to retain their identity in a world dominated economically by silver and religiously by the Catholic Church. Most studies of 16th-century Mexican crypto-Jews have focused on the merchant community centered in Mexico City, but Gitlitz looks beyond Mexico's major population center to explore how clandestine religious communities were established in the resales, the hinterland mining camps. Similarly, Gitlitz challenges traditional scholarship that has focused solely on macro issues. He combines those issues with close analysis of the complex workings of the haciendas that mined and refined silver to provide a wonderfully detailed sense of the daily experiences of secret Jews"--